Comment on 'Lorentz transformations and the wave equation' - Di Rocco, Hector Omar (2017)
In this comment we make some clarifications with respect to certain asumptions and demands required by Ricardo Heras in his paper entitled 'Lorentz transformations and the wave equation' (2016 Eur. J. Phys. 37 025603).